El cuerpo como espacio de resistencia: Foucault, las heterotopías y el cuerpo experiencial - Tulio Alexander Benavides Franco (Co-herencia: Revista de Humanidades, 2019)
Considering the diffuse character Foucault attributes to power relations, it is possible to assert that the subjection of bodies is never absolute, so they are not inexorably determined by the exercise of power. This article shows how the body, as the main target of a predominantly physical power, can eventually become the realm of un-subjection and resistance, the “place” from which that power can be resisted. This is possible in virtue of what is described in this paper as a “heterotopic condition” of the body, which would entail the exceedance and the overflow of subjection processes, and which would ultimately enable to speak about the “experiential body” as the space where the questioning of one's own subjectivity would take place.